Odpowiedzi

2009-10-16T09:12:35+02:00
2x²-7=0
2x^2=7
x^2=3,5
x= 1,87

x(5-2x)=0
5x-2x^2=0
-2x^2 +5x = 0
delta= b^2 - 4 ac= 5^2 - 4 * (-2) *0= 25
x1=(-b-pierwiastek(delta))/2a = -5-5/(-4) = -10/(-4) = 2,5
x2=(-b+pierwiastek(delta))/2a = -5 +5/(-4) = 0

(x-3)(2x+1)=0
2x^2 + x - 6x - 3 = 0
2x^2 - 5x - 3 =0
delta = (-5)^2 - 4* 2* (-3) = 25 +24 = 49
x1 = 5 - 7/4 = =1/2
x2= 5+7 /4 = 3

x-3x²=0
-3x^2 +x=0
delta= 1^2 - 4*(-3)* 0 = 1
x1= -1 -1/(-6) = -2/(-6) = 1/3
x2= -1 +1/(-6) = 0

x²-2x+1=0
delta = (-2)^2 - 4*1*1 = 4-4= 0
x1=(-b)/2a = 2/2 = 1

(3x-1)²=0
(a-b)^2 = a^2-2ab+b^2
9x^2 - 2*3x*(-1) + 1 =0
9x^2 + 6x + 1=0
delta= 36- 4*9*1= 36-36 = 0
x1= -6/18= -1/3

(5x)²=0
25x^2 = 0
x^2 = 0
x=0

x²-x√2-1=0
delta = (-√2)^2 - 4*1*(-1) = 2+4 = 6
x1= (√2-√6)/2
x2= (√2+√6)/2

x(x-4_=8
x^2 - 4x -8 =0
delta= (-4)^2 - 4* 1*(-8) = 16 + 32 = 48
√48= √16*3= 4√3
x1= (4 -4√3)/2 = 2- 2√3
x2= (4+4√3)/2 = 2+2√3